THE INFLUENCE OF BRAND IMAGE, BRAND AWARENESS AND BRAND TRUST ON BRAND LOYALTY (STUDY ON STUDENTS USING WARDAH COSMETICS) - Melli Aprillia Subastiyanti; Bambang Sutedjo (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2022)
The study aims to know and analyze the influence of brand image, brand awareness dan brand trust to brand loyalty. The object of this research is wardah cosmetics. Sources of data used in this study are primary data and secondary data.The population is stikubank semarang university students who have purchased wardah cosmetic products, with the number of samples of 98 respondents. The data testing techniques used in this study used validity tests with loading factors, realibility tests with alpha cronbach and multiple regression analysis tests. The results shiwed the brand image did not have a significant effect to brand loyalty, the brand awareness had a positive and significant effect on the brand loyalty,the brand trust had a positive and significant effect on the brand loyalty.